Dkk1 Stabilizes Wnt Co-Receptor LRP6: Implication for Wnt Ligand-Induced LRP6 Down-Regulation - Li, Yonghe; Lu, Wenyan; King, Taj D.; Liu, Chia-Chen; Bijur, Gautam N.; Bu, Guojun (PLOS ONE, 2010)
Background The low density lipoprotein receptor-related protein-6 (LRP6) is an essential co-receptor for canonical Wnt signaling. Dickkopf 1 (Dkk1), a major secreted Wnt signaling antagonist, binds to LRP6 with high affinity and prevents the Frizzled-Wnt-LRP6 complex formation in response to Wnts. Previous studies have demonstrated that Dkk1 promotes LRP6 internalization and degradation when it forms a ternary complex with the cell surface receptor Kremen. Methodology/Principal Findings In the present study, we found that transfected Dkk1 induces LRP6 accumulation while inhibiting Wnt/LRP6 signaling. Treatment with Dkk1-conditioned medium or recombinant Dkk1 protein stabilized LRP6 with a prolonged half-life and induces LRP6 accumulation both at the cell surface and in endosomes. We also demonstrated that Kremen2 co-expression abrogated the effect of Dkk1 on LRP6 accumulation, indicating that the effect of Kremen2 is dominant over Dkk1 regulation of LRP6. Furthermore, we found that Wnt3A treatment induces LRP6 down-regulation, an effect paralleled with a Wnt/LRP6 signaling decay, and that Dkk1 treatment blocked Wnt3A-induced LRP6 down-regulation. Finally, we found that LRP6 turnover was blocked by an inhibitor of caveolae-mediated endocytosis. Conclusions/Significance Our results reveal a novel role for Dkk1 in preventing Wnt ligand-induced LRP6 down-regulation and contribute significantly to our understanding of Dkk1 function in Wnt/LRP6 signaling.